2017
DOI: 10.3892/or.2017.5795
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A induces bladder cancer cell death via intrinsic apoptosis at the early phase and Sp1-survivin downregulation at the late phase of treatment

Abstract: Histone deacetylase (HDAC) inhibitors have been widely shown to result in cancer cell death. The present study investigated the mechanisms underlying the antitumor effects of the phytochemical trichostatin A (TSA), a classic pan-HDAC inhibitor, in 5,637 urinary bladder cancer cells. It was found that TSA caused cell cycle arrest at the G2/M and G1 phase accompanied by reduced expression of cyclin D1 and upregulated induction of p21. In addition, TSA induced morphological changes, reduced cell viability and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Conventional anticancer drug for UC therapy, such as vinblastine, doxorubicin, and cisplatin act during DNA synthesis and/or various phases of the cell cycle checkpoint, and produce anticancer effects [ 19 ]. There are several reports about anticancer drugs and biological compounds, such as desethylamiodarone [ 20 ], reversine [ 21 ], isoquercitrin [ 22 ], trichostatin A [ 23 ], and miconazole [ 24 ], for chemotherapy of UC. Moreover, the histone deacetylase (HDAC) inhibitor valproic acid (VPA), anticancer agent amygdalin and chalcone, which is a precursor compound for flavonoid synthesis in plants, induced cell growth inhibition via cell cycle arrest at G0/G1 or G2/M phase in UC [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional anticancer drug for UC therapy, such as vinblastine, doxorubicin, and cisplatin act during DNA synthesis and/or various phases of the cell cycle checkpoint, and produce anticancer effects [ 19 ]. There are several reports about anticancer drugs and biological compounds, such as desethylamiodarone [ 20 ], reversine [ 21 ], isoquercitrin [ 22 ], trichostatin A [ 23 ], and miconazole [ 24 ], for chemotherapy of UC. Moreover, the histone deacetylase (HDAC) inhibitor valproic acid (VPA), anticancer agent amygdalin and chalcone, which is a precursor compound for flavonoid synthesis in plants, induced cell growth inhibition via cell cycle arrest at G0/G1 or G2/M phase in UC [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (2015) revealed that the TSA-induced apoptosis in T24 bladder cancer cells is related to TRPM2 (Transient Receptor Potential Cation Channel, Subfamily M, Member 2) upregulation, which is caused by increased H3K9Ac enrichment within the TRPM2 promoter [229]. In another study by Wang et al (2017), TSA administration initially activated the intrinsic apoptotic pathway associated with phosphorylated Akt inhibition and mitochondrial membrane-potential loss, followed by downregulation of the Sp1-Survivin pathway at the late phase of treatment [230]. In vivo TSA administration in mice bearing EJ and UMUC3 bladder cancer xenografts led to a 70% tumor growth suppression and absence of detectable toxicity [227].…”
Section: Drugging the Bladder Cancer “Acetyl-proteome”: Hdac Inhibmentioning
confidence: 99%
“…TSA is a complete class I and II HDACs inhibitor [26,28], which was originally used as an antimycotic [29]. It increases histone acetylation and consequently has a strong impact on oxidative stress, cell cycle arrest, apoptosis [28,30,31], and epithelial-mesenchymal transition [32].…”
Section: Introductionmentioning
confidence: 99%